Eurasia's New Frontiers : Young States, Old Societies, Open Futures - Simons, Thomas W. (Book collections on Project MUSE., 2008)
From the Publisher: In Eurasia's New Frontiers, Thomas W. Simons, Jr., a veteran U.S. diplomat/scholar with extensive experience in the Communist and post-Communist worlds, assays the main post-1991 developments in the fifteen successor states to the USSR drat compose Eurasia. He makes a compelling case that the United States can play a large role in shaping the future of this vast and strategic region at less cost than during Soviet times. This can be achieved, however, only if U.S. policy focuses on Eurasia's fledgling individual Nation-states.